Application of the Er:YAG laser in pulpotomy for mature permanent teeth with pulpitis: An animal study - Zeqi Li; Pengfei Xin; Siyao Yang; Xiaoxing Hao; Jun Wang; Kuanshou Zhang; Qingmei Liu (PLoS ONE, 2026)
Objective To apply Erbium-doped Yttrium Aluminum Garnet (Er:YAG) laser in pulpotomy for experimentally induced pulpitis in mature permanent teeth of rats, and investigate whether Er:YAG laser can improve the effect of pulpotomy in mature permanent teeth with pulpitis. Methods Thirty-six 3-month-old male Sprague-Dawley (SD) rats were selected, with bilateral maxillary first molars as experimental teeth. 4 rats (8 experimental teeth) were selected to construct the pulpitis model. After confirming the successful establishment of the model by this method, 32 rats were randomly divided into the control group and the experimental group, and the pulpitis models were constructed in the same way. The control group(mechanical group, 16 rats, 32 experimental teeth) received pulpotomy with conventional sterile excavators. The experimental group (laser group, 16 rats, 32 experimental teeth) received pulpotomy using Er:YAG laser. At 3, 7, 14, and 28 days post-operation, four rats from each group were randomly euthanized. Pathological changes in the dental pulp were observed using hematoxylin - eosin (HE) staining. Immunohistochemical (IHC) assessment and mean optical density (MOD) measurement were performed to evaluate the expression of interleukin-1β (IL-1β) and partitioning defective protein 3 (Par3). Inter-group differences were analyzed using the Mann-Whitney U test or the independent samples t-test. Results Histological examination by HE staining demonstrated favorable pulpal repair in the laser-treated group. The total histopathological scores were significantly lower in the laser group compared to the mechanical group at days 3 and 7 post-operation ( p < 0.05). However, no statistically significant difference was observed between the two groups at days 14 and 28. IHC analysis revealed that the mean optical density (MOD) values for IL-1β were consistently lower in the laser group at all four time points ( p < 0.05), while the MOD values for Par3 were consistently higher in the laser group ( p < 0.05). Conclusion The Er:YAG laser used during pulpotomy in mature permanent rat teeth with pulpitis preserves the remaining healthy pulp tissue, reduces IL-1β expression, and enhances Par3 expression, thereby alleviating inflammation and promoting tissue repair.